Glenoid Bone Loss Directly Affects Hill-Sachs Morphology: An Advanced 3-Dimensional Analysis. Issue 9 (July 2022) - Peebles, Liam A.; Golijanin, Petar; Peebles, Annalise M.; Douglass, Brenton W.; Arner, Justin W.; Provencher, Matthew T.
Background: While the glenoid track concept presents a useful prediction for recurrent glenohumeral instability, little is known about the humeral head bony architecture as it relates to glenoid erosion in the setting of bipolar bone loss. Purpose: To (1) qualitatively and quantitatively analyze the interplay between glenoid bone loss (GBL) and Hill-Sachs lesions (HSLs) in a cohort of patients with anterior instability using 3-dimensional imaging software and (2) assess the relationships between GBL and HSL characteristics. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Patients were identified who had anterior shoulder instability with a minimum 5% GBL and evidence of HSL confirmed on computed tomography. Unilateral 3-dimensional models of the ipsilateral proximal humeral head and en face sagittal oblique view of the glenoid were reconstructed using MIMICS software (Materialise NV). GBL surface area, width, defect length, and glenoid track width were quantified. The volume, surface area, width, and depth of identified HSLs were quantified with their location (medial, superior, and inferior extent) on the humeral head. Severity of GBL was defined as percentage glenoid bone surface area loss and categorized as low grade (5%-10%), moderate grade (>10% to 20%), high grade (>20% to 30%), and extensive (>30%). Analysis of variance was then computed to determine significance ( P < .05) between severity of GBL and associated HSL parameters. Results: In total, 100 patients met inclusion criteria (mean age, 27.9 years; range, 18-43 years), which included 58 right shoulders and 42 left shoulders (84 male, 16 female). Among groups, there were 32 patients with low-grade GBL (mean GBL = 6.1%), 38 with moderate grade (mean GBL = 16.2%), 17 with high grade (mean GBL = 23.7%), and 13 with extensive (mean GBL = 34.0%), with an overall mean GBL of 18.1% (range, 5%-39%). Patients with 5%-10% GBL had significantly narrower HSLs (average and maximum width; P < .03) and deeper HSLs (average depth; P = .002) as compared with all other GBL groups, while greater GBL was associated with wider and shallower HSLs. GBL width, percentage width loss, defect length, and glenoid track width all significantly differed across the 4 GBL groups ( P < .05). Conclusion: HSLs had significantly different morphological characteristics depending on the severity of GBL, indicating that GBL was directly related to the characteristics of HSLs. Patients presenting with smaller glenoid defects had significantly narrower and deeper HSLs with less humeral head surface area loss, while greater GBL was associated with wider and shallower HSLs.